The Social Effects of Ethnic Diversity at the Local Level: A Natural Experiment with Exogenous Residential Allocation - Algan, Yann; Hémet, Camille; Laitin, David D. (Journal of Political Economy, 2016)
Relying on diversity measures computed at the apartment block level under conditions of exogenous allocation of public housing in France, this paper identifies the effects of ethnic diversity on social relationships and housing quality. Housing Survey data reveal that diversity induces social anomie. Through the channel of anomie, diversity accounts for the inability of residents to sanction others for vandalism and to act collectively to demand proper building maintenance. However, anomie also lowers opportunities for violent confrontations, which are not related to diversity.